Loan processing, credit appraisal, follow – up & recovery procedure of IFIC Bank Limited - Marzan, Nafisa (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.